Desempeño de los recolectores de cafe segun la altura de la plantacion - Villegas B, M.J.=700 1 Montoya R, E.C.; Velez Z, J.C.; Oliveros T, C.E.
(En, Es)
ilus., 6 ref.
Keywords: CAFE; COSECHA; METODOS MECANICOS; RECOLECCION; COLOMBIA; INDICADORES DE LA RECOLECCION